Recommended procedure for eye examination for infants and children of pre-school age in regular outpatient practice - Zobanová, Anna (Czech and Slovak Ophthalmology, 2017)
Vision or visual perception is a complex function of the visual analyser on all of its levels, i.e. the eye, ocular pathway and brain's visual processing centres, including the association areas. Visual acuity is only one of several parameters of vision. Others are e.g. the visual field, colour perception, contrast sensitivity, adaptation to light and darkness and spatial vision. Even for an experienced ophthalmologist it is very difficult to answer one of the most frequently asked questions of parents of a small child: “How does our child actually see?”
Keywords: diagnóza; Optometry; zrakové testy; zraková ostrost; Child, Preschool; Vision, Ocular; optometrie; Infant; Vision Tests; Observation; Age Factors; Retina; Practice Guidelines as Topic; Diagnosis; Visual Acuity; zrak; novorozenec; předškolní dítě; lidé; Humans; pozorování; Diagnostic Techniques, Ophthalmological; diagnostické techniky oftalmologické; Infant, Newborn; kojenec; věkové faktory; retina; směrnice pro lékařskou praxi jako téma